2000
DOI: 10.1108/01435120010324842
|View full text |Cite
|
Sign up to set email alerts
|

Legal information needs of lawyers in Kenya: a case study

Abstract: Reports the results of a case study undertaken as part of a doctoral research programme carried out to investigate the information needs of, and provision to, the legal community in Kenya. The case study, is based on data collected from a one‐man law firm in Kisumu, Kenya. Data were collected by interviews and observation. Although essentially a case study, the results reflect the kind of experiences and problems that lawyers in Kenya, working in single law firms, experience in accessing legal information. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Other sources identified include colleagues, government publications, personal collections, and electronic resources. The sources used by a lawyer in Kenya for his task, as observed by Otike and Matthews (2000) in their case study included legal textbooks, statutes, local and foreign reports. Makri, Blandford, and Cox (2008) also studied information seeking behaviour of lawyers in order to inform the design of an electronic information resource and suggestions were made to improve the design of digital law libraries (LexisNexis, Butterworths and Westlaw).…”
Section: Previous Studies On Lawyers' Information Seeking Behaviourmentioning
confidence: 99%
“…Other sources identified include colleagues, government publications, personal collections, and electronic resources. The sources used by a lawyer in Kenya for his task, as observed by Otike and Matthews (2000) in their case study included legal textbooks, statutes, local and foreign reports. Makri, Blandford, and Cox (2008) also studied information seeking behaviour of lawyers in order to inform the design of an electronic information resource and suggestions were made to improve the design of digital law libraries (LexisNexis, Butterworths and Westlaw).…”
Section: Previous Studies On Lawyers' Information Seeking Behaviourmentioning
confidence: 99%
“…[18] investigates the legal information needs of the general public (citizens who are not lawyers), as well as the sources (paper-based ones) they use in order to fulfil these needs, and the role of the general and law libraries, and also of legal aid centres, on this. In [19] are investigated the legal information needs of lawyers, the main purposes they are searching legal information for, the types of information required, and also sources and ways (paper-based ones) for meeting these needs; they conclude that only large law firms have extensive legal libraries and therefore sufficient access to legal information, while this does not hold for smaller law firms: for them the only practical solution, due to the inherently large volume of legal information required is co-operation among such firms, or use of courts' legal libraries. Furthermore, there is some subsequent research focusing on the demand for electronic legal information sources.…”
Section: Legal Information Provision and Analyticsmentioning
confidence: 99%
“…Otike and Mathew (2003) who found that majority of law students face the problems of lack of requisite information literacy skills required to effectively seek for information, most law students do not learn the basic information skills, they only end up using trial and error method of information search and this limits their capabilities in satisfying their information needs.…”
Section: Information Needs Of Law Students In Delta State Universitymentioning
confidence: 99%